2011
DOI: 10.1039/c1pp05014a
|View full text |Cite
|
Sign up to set email alerts
|

Targeted photodynamic therapy of breast cancer cells using antibody-phthalocyanine-gold nanoparticle conjugates

Abstract: This article is published as part of a themed issue of Photochemical & Photobiological Sciences on Drug delivery technologies and immunological aspects of photodynamic therapy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
225
1
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 308 publications
(233 citation statements)
references
References 39 publications
4
225
1
3
Order By: Relevance
“…Au has also been studied on its effects on breast cancer cells. Stuchinskaya et al, conjugated the Au nanoparticles with a phthalocyanine-antibody complex which proved to be a promising way of targeting and killing breast cancer cells by the Au nanoparticles and cytotoxic singlet oxygen producer phthalocyanine [77].…”
Section: Applications Of Metallic Nanoparticlesmentioning
confidence: 99%
“…Au has also been studied on its effects on breast cancer cells. Stuchinskaya et al, conjugated the Au nanoparticles with a phthalocyanine-antibody complex which proved to be a promising way of targeting and killing breast cancer cells by the Au nanoparticles and cytotoxic singlet oxygen producer phthalocyanine [77].…”
Section: Applications Of Metallic Nanoparticlesmentioning
confidence: 99%
“…21 These authors have shown that the nanoparticle conjugates with the anti-erbB2 antibody selectively target the erbB2 receptor that is overexpressed on SK-BR-3 breast cancer cells while having limited or no targeted photoactivity for the MDA-MB-231 breast cancer cells (breast cancer cell line without erbB2 amplification) or normal mammary epithelial cells (MCF-10A). In addition, targeting of the T antigen on the surface of human colorectal adenocarcinoma cells has been achieved using the lectin Jacalin conjugated to phthalocyanine functionalised gold nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…The HEPES and PBS 26 The jacalin or anti-HER-2 antibody conjugated C11Pc-PEG gold nanoparticles prepared for use with the SK-BR-3 cells were redispersed in serum-free Dulbecco's Modified Eagle Medium (DMEM; Invitrogen) supplemented with 1 mM L-Gln, as previously described. 11 As a control, non-conjugated C11Pc-PEG gold nanoparticles were also prepared in serum-free RPMI 1640 medium or serum-free DMEM medium, depending on the cell line used. All nanoparticle preparations were characterised using a Hitachi U-3010 UV-visible absorption spectrophotometer, appropriately diluted for in vitro experiments using either serum-free RPMI 1640 medium or serum-free DMEM medium, and stored at 4°C.…”
Section: Synthesis Of the C11pc-peg Gold Nanoparticles And Conjugatiomentioning
confidence: 99%